Analisis Dikabulkannya Dispensasi Perkawinan terhadap Anak di Bawah Umur Ditinjau Perma Nomor 5 Tahun 2019 tentang Dispensasi Perkawinan - Velany Putri Rosidy Rosih oci; Asep Ramdan Hidayat; Encep Abdul Rojak (UNISBA Press, 2023)
Abstract. Applications for dispensation of marriage at the Tasikmalaya Religious Court in 2019-2021 have increased rapidly, the existence of Perma Number 5 of 2019 concerning guidelines for adjudicating marital dispensation does not make requests for dispensation marital status decreased. In this study, there are two formulations of the problem, first 1) What are the main factors for the increase in underage child marriages in 2019-2021 at the Tasikmalaya Religious Court, and second 2) What are the considerations of judges in giving decisions on marriage dispensation letters to minors when reviewed by Perma Number 5 of 2019. The purpose of this research is to find out how the main factors are the increase in requests for marriage dispensation in the Tasikmalaya Religious Court, and to find out the judge's considerations in giving decisions for requests for dispensation marriage case. The method used in this research is a qualitative approach. This type of research is in the form of field research using a normative juridical approach, as well as determining the location of the research at the Tasikmalaya Religious Court. From the results of this study it can be concluded that: the causes of underage marriages in Tasikmalaya District are influenced by several factors, namely due to Education Factors, Tradition and Culture Factors, Promiscuity Factors, Economic Factors, and Parental Factors. The judge's decision in adjudicating the request for marriage dispensation for minors aims to avoid harm because of the parents' fear of the child doing things that are prohibited by religion. Abstrak. Permohonan dispensasi perkawinan di Pengadilan Agama Tasikmalaya pada tahun 2019-2021 meningkat dengan pesat, adanya Perma Nomor 5 Tahun 2019 tentang pedoman mengadili dispensasi perkawinan tidak menjadikan permohonan dispensasi perkawinan menurun. Dalam penelitian ini ada dua rumusan masalah yang pertama 1) Bagaimana Faktor-Faktor utama meningkatnya perkawinan anak dibawah umur pada tahun 2019-2021 di Pengadilan Agama Tasikmalaya, dan yang kedua 2) Bagaimana pertimbangan Hakim dalam memberikan putusan surat dispensasi perkawinan pada anak dibawah umur jika ditinjau Perma Nomor 5 tahun 2019. Tujuan penelitian ini untuk mengetahui bagaimana faktor–faktor utama begitu meningkatnya permohonan dispensasi perkawinan di pengadilan Agama Tasikmalaya, dan untuk mengetahui pertimbangan hakim dalam memberikan putusan bagi permohonan dispensasi perkawinan. Metode yang digunakan dalam penelitian ini adalah pendekatan kualitatif. Jenis penelitian ini berupa penelitian lapangan (field research) dengan menggunakan metode pendekatan yuridis normatif, serta penentuan lokasi penelitian di Pengadilan Agama Tasikmalaya. Dari hasil penelitian ini dapat di simpulkan bahwa: faktor penyebab terjadinya perkawinan di bawah umur di Kecamatan Tasikmalaya dipengaruhi oleh beberapa faktor yaitu karena Faktor Pendidikan, Faktor Tradisi dan Budaya, Faktor Pergaulan Bebas, Faktor Ekonomi, dan Faktor Orang tua. Putusan Hakim dalam mengadili permohonan dispensasi perkawinan pada anak di bawah umur bertujuan untuk menjauhi kemudharatan karena kekhawatiran orang tua terhadap sang anak melakukan hal yang dilarang oleh Agama.